Analysis of Biological and Chemical Parameters in Alkaline Water of Various Brands in Indonesia - Fitri Rokhmalia; Pratiwi Hermiyanti (International Journal of Advanced Health Science and Technology, 2022)
Humans need drinking water in life and up to 70% of the human body is water. Consuming enough mineral water for the body can help the process to facilitate digestion, regulate metabolism, regulate food substances in the body and regulate body balance. 46.1% of adolescents from 1200 respondents studied when feeling thirsty prefer instant drinks compared to consuming mineral water, this causes mild dehydration with symptoms: dry lips up to the throat, body weakness. This study aimed to analyze the levels of biological and chemical parameters in alkaline water of various brands in Surabaya which were coded KW, M, P and T. This study was experimental with a post-test only control group design. The research data were statistically tested using one-way ANOVA with the aim of analyzing the levels of biological (E.Coli and MPN Coliform) and chemical (arsenic, fluoride and total chromium) parameters in alkaline water (KW, M, P, T). E.coli parameters in 4 types of alkaline water which were coded KW, M, P and T met the standard requirements, namely 0 colonies/100 ml. Chemical parameters namely arsenic met the requirements of 0-0.1 ppm, fluoride met the requirements of 0.01-1.5 ppm and total chromium met the requirements of 0.01-0.05 ppm. In accordance with the results of the examination, it is revealed that the process of making and producing alkaline water of various brands in the market under study are following the Good Food Production Methods (CPPB), thus there is no E. Coli and MPN Coliform content. Suggestions can be given to future researchers and the community; future researchers need to conduct further research on other brands of alkaline water in various areas with a wider range while the community needs to be more selective and smart in choosing alkaline water to be consumed to maintain a healthy body so they can benefit it at an affordable price